Leo Ruhnau conducting acid analysis in Dow Chemical Company laboratory - Dow Chemical Company (1944)
General view of technician Leo Ruhnau using an apparatus to determine the percentage of hydrochloric acid in Dowell acids at a Dow Chemical Company laboratory.
Keywords: Employees; Industries; Scientific apparatus and instruments; Dow Chemical Company; Glassware; Laboratories; Ruhnau, Leo